Analisis Komparatif Penerapan Akad Wadiah Dalam Produk Tabungan Syariah Dan Dampaknya Terhadap Loyalitas Nasabah - Qonita Hidayati; Mohd Winario; Rifqil Khairi (EL-EMIR Institute, 2025)
This study aims to conduct a comparative analysis of the implementation of the wadiah contract in savings products at several Islamic banks in Indonesia and examine its impact on customer loyalty. Wadiah is a safekeeping (deposit) contract without compensation, commonly applied in Islamic banking savings products. This research uses a descriptive qualitative approach with case studies at three prominent Islamic banks: Bank Syariah Indonesia (BSI), Bank Muamalat, and Bank Mega Syariah. Data were collected through in-depth interviews with management and customers, as well as product documentation. The results show that the application of the wadiah contract varies in terms of transparency, hibah (bonus) incentives, and treatment of customer funds. These differences significantly affect customers' perceptions of fairness, comfort, and trust, ultimately influencing varying levels of customer loyalty. This study recommends standardizing the implementation of the wadiah contract to avoid sharia ambiguity and maintain public trust in Islamic banks.